Relative Influences of Review and Engagement Auditor Rotation on Audit Quality: Evidence from China - Kim, Sang Ho; Xi, Jianqun (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study focuses on the effects of audit partner rotation on audit quality (AQ) in China. In particular, we examine the effects of review auditors (RAs) and engagement auditors (EAs) on AQ when they voluntarily and mandatorily rotate. Design/Methodology/Approach: The data in this study are retrieved from the Chinese Stock Market and Accounting Research (CSMAR) database. We develop an OLS regression model and logit model respectively to test the hypotheses developed. Finally, we have 13,856 firm-year observations collected for the first regression model, and 16,893 firm-year observations gathered for the second logit model from 2003 to 2015. Research findings: Findings show that RAs are more likely to behave opportunistically to retain clients by weighing up the benefits and costs of compromising audit quality in the first year after a rotation. The results imply that RAs may have an incentive to acquiesce the clients’ accounting irregularities in their first year of audit engagement when they are mandatorily rotated. However, we do not find this trend in terms of EAs’ rotation, suggesting that EAs are less affected by the auditor-client relationship compared to RAs. In addition, we find that RAs are less likely to issue modified audit opinions (MOPI) as the magnitude of negative discretionary accruals (DA) increases when they are voluntarily rotated. Theoretical contribution/Originality: Previous studies have investigated the relationship between mandatory audit partner rotation and audit quality. The results are mixed and inconclusive. Our study contributes to the extant literature by considering RAs’ opportunistic behaviour after mandatory rotation, which has not been explored in previous studies. In China, only a few studies have examined the relationship between mandatory audit partner rotation and audit quality. Our study is one of the first study focusing on the RA’s influence on AQ. Practitioner/Policy implication: The findings of our study can help Chinese authorities, listed firms and academics gain more understanding on whether mandatory audit partner rotation improves audit quality in practice. Since RAs have greater incentive to retain the existing client, we propose that RAs should bear more responsibility for the audit work, instead of the equally shared responsibility with EAs. Research limitation/Implications: Our study is subject to some limitations. First, our study adopts the performance-adjusted discretionary accruals as a proxy for audit quality. However, there can be a measurement error in estimating discretionary accruals. Second, we focus on the auditor rotation and exclude the case of audit firm rotation. Since the AQ can be affected by various factors, audit firm rotation can also affect AQ. Third, although we test the relative effects of RAs and EAs in audit work, we do not examine the effect of RAs’ characteristics such as their professional experience, educational background, and years of service. AQ can be affected by RAs’ characteristics. Keywords: Auditor Rotation, Audit Quality, China, Review Auditors, Engagement Auditors JEL Classification: G0